Preparation of Poly Methyl Acrylate Membrane by Template Polymerization Method - Awasthi, Rita; Awasthi, Sanjay; Tripathi, Swati (Asian Journal of Chemistry, 2010)
Poly methyl acrylate membrane in bulk has been synthesized in the presence of poly methyl methacrylate (template) at 65 ± 0.1 ºC for 1.5 h using benzoyl peroxide as an initiator. The present work focuses the synthesis of hydrophobic polymeric membrane through template polymerization, in order to confirm the nature of polymeric membrane.